2016
DOI: 10.3847/0004-637x/821/1/48
|View full text |Cite
|
Sign up to set email alerts
|

Low-Mass Active Galactic Nuclei With Rapid X-Ray Variability

Abstract: We present a detailed study of the optical spectroscopic properties of 12 active galactic nuclei (AGNs) with candidate low-mass black holes (BHs) selected by Kamizasa et al. through rapid X-ray variability. The highquality, echellette Magellan spectra reveal broad Hα emission in all the sources, allowing us to estimate robust viral BH masses and Eddington ratios for this unique sample. We confirm that the sample contains low-mass BHs accreting at high rates: the median M BH = 1.2 × 10 6 M ⊙ and median L bol /L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…1 is the minimum velocity width of Hβ (see Equation (15) in Paper IV). We note that the minimum observed FWHM value of Hα (which is comparable to Hβ) is~-10 km s 3 1 among low-mass AGNs (Greene & Ho 2007;Ho & Kim 2016). Indeed, this limit is consistent with the saturation trend of b r H (Figure 6(a)).…”
Section: Where S Bsupporting
confidence: 85%
“…1 is the minimum velocity width of Hβ (see Equation (15) in Paper IV). We note that the minimum observed FWHM value of Hα (which is comparable to Hβ) is~-10 km s 3 1 among low-mass AGNs (Greene & Ho 2007;Ho & Kim 2016). Indeed, this limit is consistent with the saturation trend of b r H (Figure 6(a)).…”
Section: Where S Bsupporting
confidence: 85%
“…of ∼ 10 3 M ) BHs. The virial BH masses of the 10 low-mass AGN from Ho & Kim (2016) are found to follow the M BH − σ * relation (if the considerably large scatter in the pseudobulge regime is considered, e.g., Ho & Kim 2016; grey squares in Fig. 10), as found for other samples of low-mass AGN (also included in Table 3 and Fig.…”
Section: X-ray Weak Imbhs: Hiding Behind the Dust?mentioning
confidence: 58%
“…However, this is not the case for the M BH −M bulge relation: the BH mass of IMBHs/low-mass AGN tends to be lower at a given bulge mass than expected from an extrapolation of the relation found for classical bulges (e.g., Greene et al 2008;Jiang et al 2011;Graham & Scott 2013Baldassare et al 2015Baldassare et al , 2017Nguyen et al 2017). SMBHs in inactive galaxies with pseudobulges (Hu 2008;Kormendy & Ho 2013) and spiral galaxies with megamaser BH mass measurements (Greene et al 2010;Läsker et al 2016) are also found to fall below the M BH − M bulge relation of early-type galaxies (Kormendy & Ho 2013), which suggests that most IMBHs/low-mass AGN are hosted by late-type galaxies (Greene & Ho 2007a;Ho & Kim 2016). Finally, low-mass late-type galaxies tend to lie as well below the M BH − M * relation compared to bulge-dominated and elliptical (early-type) galaxies (Reines & Volonteri 2015), which could be explained by IMBH quenching of the star formation during an early gas-rich phase in the life of the dwarf galaxy (Silk 2017).…”
Section: X-ray Weak Imbhs: Hiding Behind the Dust?mentioning
confidence: 88%
See 2 more Smart Citations